PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 005 SEDINGINAN - Reni Endriani; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was aimed to increase students achievement of social lesson in IV grade year of 2014/2015. The subject of this research in students IV grade of state Elementary School 005 Sedinginan which is total of 20 students, consisted of 11 girls and 9 boys. This was a classroom research which has two cycles which was conducted on March 19th to April 16th 2015. The data shown that either learning process or students achievement increased. This was found from students and teachers scores in learning process increased. First cycle at the first meeting teacher’s activity was 67,5%categorized as good and increased 7,5% at the second meeting as 75% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 87,5% categorized as very good and in the second meeting it increased as 5% so the percentage became 92,5% categorized as very good. While students activities in learning process also increased. At the first cycle in the first meeting, the percentage of students activities was 63,9% categorized as good and the second meeting it increased as 8,6% so became 72,5% categorized as good. At the second cycle in the first meeting it increased to 86,1% categorized as very good. At the second meeting the percentage of students’ activities increased as 5,5% became 91,6% categorized as very good. However, students’ achievement also increased. The basic score of daily examination as 7,95% which 12 students passed and 8 students failed. The ending of daily examination was 60% and the average 71,25 on the passing grade. The second daily examination also increased from basic score of as8,42% which 16 students passed and 4 students failed. The ending of second daily examination was 80% and the average was 77,25. Based on the explanation above it can be concluded that the implementation cooperative learning STAD thype to increase students achievement in social lesson of students IV grade of State SDN 005 Sedinginan.Key Words : Cooperative Learning STAD Thype, Social Lesson Learning Outcomes